2021
DOI: 10.1108/ijchm-02-2021-0132
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis in hospitality and tourism: a thematic and methodological review

Abstract: Purpose This study aims to conduct a systematic review and critically analyze the sentiment analysis literature in hospitality and tourism from methodological (data sets and analyzes) and thematic (topics, theories, key constructs and their relationships) perspectives. Design/methodology/approach Qualitative thematic review and quantitative systematic review were performed on 70 papers obtained from hospitality and tourism categories of two databases, namely, Web of Science and Scopus. Findings A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 102 publications
(191 reference statements)
2
47
0
1
Order By: Relevance
“…Systematic review of literature is a recognized method widely used in hospitality and tourism research to examine the significant contributions in a specific field of study and investigate the scientific debate in a specific scientific journal (Chu et al , 2020; Mariani and Baggio, 2022; Mehraliyev et al , 2022; Nusair, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Systematic review of literature is a recognized method widely used in hospitality and tourism research to examine the significant contributions in a specific field of study and investigate the scientific debate in a specific scientific journal (Chu et al , 2020; Mariani and Baggio, 2022; Mehraliyev et al , 2022; Nusair, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, technologies, such as mobile apps, robots and the internet of things, are expected to be adopted and to provide personalized services (Pelet et al, 2021;Mercan et al, 2020). For example, the statistical data and sentiment generated by tourists can be collected from apps and analyzed through various methods for better service (Han et al, 2021;Mehraliyev et al, 2021). Interactive location-based activities can be considered by AR developers.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…It might be also useful for destination management organizations and tourism bodies to explore the disease statistics and news sentiment index on a weekly basis and develop policies, programs, and marketing plans considering their effects of attitudes toward tourism. The previous literature describes the effects of online sentiment on tourism demand [17][18][19][20]. Therefore, the study results provide an opportunity to regress tourism demand on different sentiment measures with the moderating effects of COVID-19 statistics and generate out-of-sample tourism demand forecasts.…”
Section: Discussionmentioning
confidence: 96%
“…Sentiment analysis is a way to gauge peoples' attitudes quickly and account for change over time. Furthermore, several recent studies suggested that online sentiment can be used as an indicator of tourism demand [17][18][19]. Therefore, it is important to model and forecast future tourism demand by exploring the effects of COVID-19 statistics on sentiments toward tourism.…”
Section: Introductionmentioning
confidence: 99%